From #mcdonaldsfail to #dominossucks. (3rd August 2015) - Guidry, Jeanine D.; Messner, Marcus; Jin, Yan; Medina-Messner, Vivian
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to analyze the crisis information posted by publics on the social media platform Instagram about leading fast food companies as well as the responses by the companies and their general use of Instagram. Design/methodology/approach – In two quantitative content analyses, 711 Instagram posts were identified in a two-week constructed time period that related to the ten largest fast food chains in the world. Findings – It was found that negative content about these companies is posted by customers and employees alike and that the negative tonality primarily stems from issues with service and the work environment. The study also showed that the companies are just starting to discover Instagram and have very little engagement with users. None of the companies responded to the negative posts of customers and employees. Research limitations/implications – The analysis only evaluated posts with negative hashtags about ten fast food companies. Future research should expand the analysis to all posts about a certain sector as well as expand the scope of the research beyond the fast food sector. Practical implications – The results of the study are a call-to-action for public relations professionals to engage with their publics on Instagram and actively use the app as a pre-crisis monitoring and crisis response tool in their social media plans. Originality/value – Instagram is a fast-growing social media channel, yet research into this platform is lacking. The findings of this study should be a challenge to public relations practitioners to put Instagram next to Facebook and Twitter at the center of their social media strategy.